High Efficiency Vibrational Technology (HEVT) for Cell Encapsulation in Polymeric Microcapsules - Silvia Pisani; Rossella Dorati; Ida Genta; Enrica Chiesa; Tiziana Modena; Bice Conti (MDPI AG, 2020)
Poly(methyl-methacrylate) (PMMA) is a biocompatible and non-biodegradable polymer widely used as biomedical material. PMMA microcapsules with suitable dimension and porosity range are proposed to encapsulate live cells useful for tissue regeneration purposes. The aim of this work was to evaluate the feasibility of producing cell-loaded PMMA microcapsules through "high efficiency vibrational technology" (HEVT). Preliminary studies were conducted to set up the process parameters for PMMA microcapsules production and human dermal fibroblast, used as cell model, were encapsulated in shell/core microcapsules. Microcapsules morphometric analysis through optical microscope and scanning electron microscopy highlighted that uniform microcapsules of 1.2 mm with circular surface pores were obtained by HEVT. Best process conditions used were as follows: frequency of 200 Hz, voltage of 750 V, flow rate of core solution of 10 mL/min, and flow rate of shell solution of 0.5 bar. Microcapsule membrane allowed permeation of molecules with low and medium molecular weight up to 5900 Da and prevented diffusion of high molecular weight molecules (11,000 Da). The yield of the process was about 50% and cell encapsulation efficiency was 27% on total amount. The cell survived and growth up to 72 h incubation in simulated physiologic medium was observed.